Kombinasi Metode Digital dengan Pendekatan Hybrid Learning untuk Mengembangkan Suasana Belajar yang Menyenangkan pada Mata Pelajaran Pancasila di MI/SD - Moch. Farich Alfani (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The problem of Generation Z who do not like to read texts prefer learning with audio-visual means compared to narrative texts is one of the problems that requires innovative solutions to develop a learning strategy in teaching and learning activities, including Pancasila learning in elementary schools after the Covid-19 pandemic. This study aims to describe the learning strategy with a combination of digital methods with a hybrid learning approach to develop a pleasant learning atmosphere in Pancasila learning in elementary school. This study is a field research with a qualitative approach. Data collection was done through observation, interview, and documentation techniques. The collected Data were checked for validity by triangulation, negative case analysis, and member-check techniques before being analyzed by Miles, Huberman, and Saldana analysis models, namely: data presentation, data condensation, and verification and conclusion. The results of this study indicate that the strategy of combining digital methods with hybrid learning approaches to develop a pleasant learning atmosphere in Pancasila subjects at the elementary school level can be done by allocating time between 30% for online and 50% for offline, in this innovation of combining digital methods with hybrid learning approaches, students are more enthusiastic in following learning because the activities are not only monotonous in the use of methods and media used. It is hoped that the combination of these approaches can continue to be applied by the next generation.